9 Box Model Talent Management: Potential Review Assessment on Bank Employees - Ketut Ayu Pratithi Widnyanadita; Dewi Syarifah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Potential review individual assessment research is carried out as a form of talent management activity to obtain a comprehensive picture of the subject's potential and what competencies that still need to be developed. The tool used to determine potential competencies and their current and long-term contribution to the organization is the 9-box model. The subjects in this study were 1 person who was an employee at PT Bank X. The subject had just served as a Corporate Culture Supervisor. This study used two data collection methods, the test method (psychological test kits and work samples) and non-test (interview). Data were analyzed using descriptive analysis and qualitative analysis. The results of the study show that in the 9-box model analysis, the subject is included in the